EXPLORATORY ANALYSIS OF PUBLIC INTEREST IN HAJJ SAVINGS (CASE STUDY AT BSI ENREKANG BRANCH) - Warda, Warda; Syarifuddin, Ahmad Dzul Ilmi (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2025)
This study aims to analyze the factors influencing public interest in Hajj savings at Bank Syariah Indonesia (BSI) Enrekang Branch and the challenges faced in its utilization. The research employs a qualitative case study approach with data collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing with source and technique triangulation for validity testing.The findings show that public interest is influenced by trust in the bank, ease of registration processes, economic conditions, promotion, and service quality. The main challenges identified are limited access to branch offices and insufficient public understanding of Islamic banking products and principles. These findings indicate the need for enhanced education and equitable service distribution to optimize community participation in Hajj savings.